Survey of potential factors involved in the low frequency of CP5 and CP8 expression in Staphylococcus aureus isolates from mastitis of dairy cattle from Argentina, Chile, and Uruguay - Ambroggio, Maria Belen (2018)
Staphylococcus aureus produces capsular polysaccharides (CPs) both in vivo and under defined culture conditions being serotypes 5 and 8 the most prevalent. S. aureus isolates that fail to produce CP5 or CP8 are defined as non-typeable (NT). Loss of capsule expression, however, may lead to S. aureus persistence in a chronically infected host. The prevalence of NT strains of S. aureus isolated from bovine mastitis varies according to the geographic origin of the strain. The aims of this work were to detect phenotypically and genotypically the capsular profile of 144 S. aureus isolated from bovine mastitis in Argentina, Chile, and Uruguay and explore the factors that are considered to be associated with capsule expression as presence of IS257, IScap, and agr typing of non-related collection. The detection of the IS257, IScap, cap genes, and agr typing was performed using PCR. The detection and quantification of capsular polysaccharide production were performed by ELISA assays. We found that 96% of the S. aureus isolates investigated carried cap5(8) genes but over 75% of strains do not express capsule in the three countries studied. However, only 6 isolates from Argentina carried the IScap element that totally suppressed the expression of the capsule, suggesting that other factors could influence on CP expression. Moreover, the agrI/NT association was statistically significant suggesting that this profile is a phenomenon observed not only in other parts of the world but also in our region.